Improved Salt Tolerance and Morphological Variation in Indica Rice (Oryza sativa L.) Transformed with a Catalase Gene from E. coli - Prodhan, Shamsul H.; Hossain, A.; Nagamiya, Kenji; Komamine, Atsushi; Morishima, Hiroko (Plant Tissue Culture and Biotechnology, 2009)
In an attempt to improve the salt tolerance of rice, we introduced katE, a catalase gene of Escherichia coli, into the indica rice cultivar Kasalath. Transformation was carried out using Agrobacterium tumefaciens strain EHA101 harboring a binary vector pIES6/Hm/katE which contains genes for catalase katE, hygromycine resistance gene HPT and kanamycin resistance gene NPTII in the T-DNA region. With the inclusion of acetosyringone, higher amount of transgenic cells and regenerated plants were obtained. Transformation was confirmed by PCR with katE and HPT primer. Transgenic plants at a very young stage (three - four days) were able to grow up to 15 days in 100 mM NaCl solution and seven days in 250 mM NaCl solution whereas control plants died within five days in 100 mM and seven days in 50 mM NaCl. Plants stressed for four weeks could survive for a long time and were able to flower. Different morphological characters varied in transgenic compared to control plants. Introduction of katE gene significantly improved the salt tolerance of the transgenic indica lines which could mature and set seed under stress. Key words: Rice, Oxidative stress, Enhanced salt tolerance, Transformation, Morphological variation D.O.I. 10.3329/ptcb.v18i1.3266 Plant Tissue Cult. & Biotech. 18(1): 57-63, 2008 (June)